MATERIAL SELECTION FOR AUTOMOTIVE FENDER DESIGN USING INTEGRATED AHP-TOPSIS - Arep@ Ariff, Hambali Bin; Chia Min, Goh; Mohamad Tar, Amira Farhana Binti; Jaafar, Rosidah Binti (Journal of Advanced Manufacturing Technology (JAMT), 2016)
<span style="font-size: 10pt; font-family: ’Palatino Linotype’,’serif’; color: #231f20; mso-fareast-font-family: ’Palatino Linotype’; mso-bidi-font-family: ’Palatino Linotype’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">This paper presented the integration of (Analytic Hierarchy Process) AHP and (Technique of Order Preference by Similarity to Ideal Solution) TOPSIS in material selection process of an automotive fender design. The selection of material for automotive fender was focused on lighter materials due to new trend in producing light weight vehicles in automotive industry. The main objective is to determine the best material for automotive fender using the integrated AHP-TOPSIS approach by identifying important criteria in material selection of the automotive fender. The important criteria considered were Performance, Cost, Weight and Manufacturing criteria. Three different types of material categories were considered namely High Strength Steel,<span style="font-size: 10pt; font-family: ’Palatino Linotype’,’serif’; color: #231f20; mso-fareast-font-family: ’Palatino Linotype’; mso-bidi-font-family: ’Palatino Linotype’; mso-ansi-language: EN-GB; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="EN-GB"> Aluminium<span style="font-size: 10pt; font-family: ’Palatino Linotype’,’serif’; color: #231f20; mso-fareast-font-family: ’Palatino Linotype’; mso-bidi-font-family: ’Palatino Linotype’; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;"> Alloy and Thermoplastic in the selection process. AHP method was used to determine the weight of the selection criteria and followed by TOPSIS method to perform the ranking of alternatives. The results showed that PPE/PA/989 resin is the best material for the automotive fender based on the criteria chosen. As a conclusion, the integrated AHP-TOPSIS approach was proven in assisting engineers in evaluating and determining the best material for the automotive fender which involved many criteria and alternatives in the material selection process